INDONESIAN MUSLIM DIASPORA FOR THE ADVANCEMENT OF WORLD PEACE - Achmad Sururi (TAWASUT, 2017)
AbstractWorld peace is still something that is not easily realized. One ofserious threats on world peace comes from acts of terrorism. Actsof terrorism in the name of religion are being brought in somecountries. The number of victims of terrorism continues to increaseover time. And the present moment is the worst condition throughoutrecorded history. Acts of terrorism in the development not onlytargets the State with all its symbols, but also the civil society. Soyou could say the conditions today are very asymmetrical.Departing from these conditions, then Indonesia as a country witha large Muslim population, it is appropriate to perform a mission ofworld peace. The mission of world peace can be played bymaximizing the role of the citizens of Indonesia diaspora. Thediaspora has the potential to develop a peace mission which initself will improve the reputation of Indonesia.Keywords: diaspora; Indonesian muslim; world peace